Fabrication and characterization of chitosan-coated sisal fiber – Phytagel modified soy protein-based green composite. (August 2019) - Verma, Akarsh; Singh, Chhavi; Singh, VK; Jain, Naman
In this article, a detailed systematic methodology to fabricate and characterize the diverse properties of soy protein and sisal fiber reinforced green composites has been presented. After fabrication by hand lay-up and solution casting method, these composites with varying sisal fiber weight percentages (0, 3, 4, 5, 6, 7 and 10) were put to various characterization tests. The surfaces of sisal fiber were treated with sodium hydroxide to enhance its interfacial bonding properties. The fabricated samples were examined on the basis of microstructural tests that included the scanning electron microscopy; followed by the mechanical (tensile) and physical (water absorption) tests. Finally, the thermal tests were performed that involved the thermogravimetric analysis, differential thermal analysis and dynamic mechanical analysis tests. The phytagel modified soy protein-based composite with 5 wt.% of sisal fiber content was confirmed to be the best of all compositions under this scrutiny, which was authenticated by the micro-structural and mechanical tests. To further enhance the mechanical, physical and thermal properties of fabricated composites, chitosan coating was applied on them.